2023
DOI: 10.2147/ijgm.s409478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Profile of COVID-19 Patients with Omicron Variant Admitted in a Tertiary Hospital, Central China

Abstract: Purpose Omicron, a variant of COVID-19, is becoming a major issue of global concern. Its high transmissibility may bring challenges to the distribution of health care in a large population country like China. Investigating the behavior of the virus in the Chinese population will certainly help to plan for the upcoming surge of Omicron. Therefore, we made a preliminary analysis of the clinical and epidemiological characteristics of suspected cases of Omicron at the early stage of the surge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…In our training set, the main symptoms were cough (113, 71.52%), fever (110, 69.62%), chest tightness (81, 51.27%), and pharyngalgia (17, 10.76%), which was similar to the study population in Miao et al [ 22 ]. The CURB-65 and PSI scores in the 90-day death group were higher than in the survivor group ( p < 0.001).…”
Section: Discussionsupporting
confidence: 70%
“…In our training set, the main symptoms were cough (113, 71.52%), fever (110, 69.62%), chest tightness (81, 51.27%), and pharyngalgia (17, 10.76%), which was similar to the study population in Miao et al [ 22 ]. The CURB-65 and PSI scores in the 90-day death group were higher than in the survivor group ( p < 0.001).…”
Section: Discussionsupporting
confidence: 70%
“…Our findings are consistent with those of other studies that have reported a higher prevalence of the Omicron SARS-CoV-2 among females compared to males in Malawi, the United States of America and Zambia [ 34 , 46 , 47 ]. However, other studies have reported contrasting results, with more males being infected with the Omicron SARS-CoV-2 compared to females [ 48 ] with consistently more severe disease in males than in females [ 49 , 50 ]. These differences could be explained by the differences in transmission dynamics between the different settings, although our relatively limited sample size could also have influenced our findings.…”
Section: Discussionmentioning
confidence: 99%